Correlations Between Occlusion Presure and Muscle Activity with K7 System - Alina Apostu; Corina Cristescu (Romanian Society of Oral Rehabilitation, 2010)
Trying to measure the occlusal pressure always represented a challenge for researchers, the methods used were various from simple to complex ones. It is very important to be able to appreciate the forces born at the occlusal level through both diagnose and treatment point of view, knowing that every dental treatment (filling till complex rehabilitation) needs excessive attention in occlusion relationship reconstruction. This was the main purpose of our study concerning forces developed in occlusion and their distribution. The utility of research is evident in occlusion rebalancing treatment.